Pengaruh Citra Merek, Harga, Iklan Televisi terhadap Keputusan Pembelian Mie Instan Sehat Lemonilo pada Mahasiswa Fakultas Ekonomi Universitas Islam “45” - Farah Nurlela; Isti Pujihastuti (Fakultas Ekonomi Universitas Islam 45, 2022)
This study was to determine the effect of brand image, price, and television advertising on purchasing decisions for healthy Lemonilo instant noodles for Unisma Economics faculty students. The research method used in this research is quantitative description, the sample of this study is 100 respondents. The results of the analysis show that the calculated F value is 25.345 with a significant level of 0.000. So the variables of brand image, price, and television fish simultaneously influence the purchase decision. The partial test results of the hypothesis test that the brand image variable is not significant to the purchase decision t test, namely T count on the brand image variable X1 = 0.690 with a significant level of 0.492 less than 0.05. The price variable has a significant effect on purchasing decisions, the value of the t test is T calculated on the price variable X2 = 3.706 with a significant level of 0.000 greater than 0.05. And television advertising variables have a significant effect on purchasing decisions, this is evidenced by the value of the t test, namely T count on television advertising variable X3 = 3.120 with a significant level of 0.002 greater than 0.05. From the results of this study, the contribution of brand image, price, and television advertising variables is 42.5% while the remaining 57.5% is influenced by variables or other factors not examined in this study.